Sustaining civic space in times of COVID-19: Global trends - Jasmin Lorch; Monika Onken; Janjira Sombatpoonsiri (German Institute of Global and Area Studies (GIGA), 2022)
In this paper we challenge the conventional wisdom that COVID-19 and related legal restrictions invariably reinforce a global trend of shrinking civic space. We argue that the legal guarantee of civil liberties is not the sole factor configuring civic space. Instead, civic space is best understood as being configured by three interacting components: 1) the legal guarantee (or restriction) of civil liberties, that is, rights-based space; 2) socio-economic needs that configure needs-induced space; and, 3) civil society activism. During the pandemic needs-induced space for civil society has emerged both from the health crisis and because restrictive government responses have had severe socio-economic side effects on people's livelihoods. These socio-economic conditions, along with civic discontent over restrictions on civil liberties, have driven civil society engagement in the form of both relief and advocacy/protest activism. Along with the structural condition of needs-induced space, this civil society activism has worked to sustain civic space.
Keywords: 300; COVID-19; shrinking space; civic space; civil society; activism